High-performance neodymium iron boron preparation method based on reduced heavy rare earth
By contacting the diffusion agent in the state of raw material powder in the iron boron magnet, and forming coating during the sintering process, the problem of uneven distribution of heavy soil is solved, and the homogeneity and efficiency of the diffusion of the inner and outer crystal circles in the magnetic body are realized. Essence
Patent Information
- Application Number
- CN202411493052.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, when preparing high coercive neodymium iron boron magnets, the distribution of heavy rare earths in thicker magnets is uneven, resulting in poor waste and grain boundary diffusion effects.
By fully contacting the diffusing agent in the raw material powder state and forming a coating during the sintering process, comprehensive and homogeneous grain boundary diffusion is achieved.
It improves the homogeneity of the diffusion of the surface layer and the inner layer of the magnet, saves the amount of heavy soil, simplifies the process process, and improves efficiency.
Smart Images

Figure BDA0005100580280000081 
Figure BDA0005100580280000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of NdFeB, and in particular to a method for preparing high-performance NdFeB based on reduced heavy rare earth. Background Art
[0002] NdFeB magnets are widely used in electronics, automobiles, wind power generation and other fields due to their excellent magnetic properties. It has been found that adding an appropriate amount of heavy rare earth elements to NdFeB magnets can significantly improve the coercivity of the material, thereby enhancing the stability and service life of the magnet at high temperatures. This is because heavy rare earth elements can form phases with high magnetocrystalline anisotropy, which helps to prevent the movement of magnetic domain walls and thus improve the coercivity. Elements such as Dy and Tb are essential for improving the coercivity of magnets, that is, the ability to resist demagnetization; however, heavy rare earth elements are scarce and expensive, and their mining and processing processes have a great impact on the environment, which makes reducing or replacing heavy rare earth elements an important research direction in the preparation of NdFeB magnets.
[0003] In the prior art, grain boundary diffusion technology is generally used to reduce the usage of heavy rare earth elements while ensuring performance.
[0004] Comparative Document 1: For example, the patent document with application number "2023107829965" and titled "Method for preparing high coercive force neodymium iron boron magnet and prepared neodymium iron boron magnet", which tempers the diffused magnet after diffusion through the combination of coating step, diffusion step and tempering step to obtain a neodymium iron boron magnet with high coercive force.
[0005] Comparative Document 2: For example, the patent document with application number "2020103371742" and titled "A Method for Grain Boundary Diffusion of Heavy Rare Earth Elements in Sintered NdFeB Magnets" adopts a two-step diffusion method. The first step increases the content and distribution continuity of the grain boundary phase of the NdFeB magnet through grain boundary diffusion of low-melting point alloys, and lowers the melting point of the grain boundary phase, which provides a favorable diffusion channel for the second step of diffusion of heavy rare earth elements at higher temperatures.
[0006] Comparative Document 3: For example, the patent document with application number "2024108405211" and name "Method for Preparing Sintered NdFeB Magnets Using Heavy Rare Earths", after the heavy rare earth diffusion source material is coated on the surface of the green body and scraped flat, the inward concave surface microstructure can accommodate a certain amount of heavy rare earth diffusion source material, and the area with the surface microstructure is coated with more heavy rare earth diffusion source material than the area without the surface microstructure, so that different areas on the surface of the green body can have different heavy rare earth contents.
[0007] Through the understanding of the existing technology, the existing grain boundary diffusion technology uses certain means to form a heavy rare earth film layer on the surface of the formed NdFeB magnet embryo, and then uses subsequent means to diffuse the heavy rare earth into the magnet to achieve grain boundary diffusion; however, for thicker magnets, that is, magnets with a thickness of more than 10 mm, due to the thickness of the magnet, it is necessary to continuously repeat the above-mentioned film forming layer and diffusion steps to support the penetration of heavy rare earth into the magnet. Since the heavy rare earth penetrates from the surface to the inner layer, this leads to the accumulation of heavy rare earth on the surface of the magnet, while the inner layer is sparse and the overall distribution is uneven, which will cause a waste of heavy rare earth and is not conducive to the effect of grain boundary diffusion. Summary of the invention
[0008] In order to solve the above technical problems, the present application provides a method for preparing high-performance NdFeB based on reduced heavy rare earth.
[0009] The method for preparing high-performance NdFeB based on reduced heavy rare earth comprises the following steps:
[0010] S1, smelting and casting;
[0011] The raw materials are melted in proportion under inert gas protection conditions, and after melting, they are quickly poured into a preheated copper mold and solidified by rapid cooling to form an ingot to obtain a fine and uniform grain structure;
[0012] S2, hydrogen crushing and ball milling;
[0013] The ingot is subjected to hydrogen crushing treatment to decompose it into fine powder, and the powder is dry-milled under argon protection to obtain a powder particle size of 10-20 μm;
[0014] S3, coating formation;
[0015] The ball-milled powder is immersed in an electrolyte containing a diffusant, and the solution is uniformly attached to the powder surface by adjusting the voltage and time, and the coating thickness is controlled to be 1 to 3 μm. The electrolyzed powder is then placed in a drying oven until the powder is completely dry.
[0016] S4, sintering;
[0017] The dried powder is pre-pressed to form a green body with a certain density and shape, and the green body is placed in a sintering furnace protected by vacuum or inert gas for sintering;
[0018] S5, aging treatment.
[0019] As a further technical solution of the present invention, in S1, the raw materials include main material, light rare earth, heavy rare earth and transition metal, wherein the mass ratio of the main material, light rare earth, heavy rare earth and transition metal is (96-97): (1-2): (0.5-1.5): (0.5-1).
[0020] As a further technical solution of the present invention, in S1, the main material is Nd2Fe14B, the light rare earth is one of Ce and La, the heavy rare earth is one of Dy and Tb, and the transition metal is one or more of Co, Cu, Al and Ga.
[0021] As a further technical solution of the present invention, in S1, the smelting temperature of the raw materials is 1500° C. to 1600° C., and the time is 60 minutes.
[0022] As a further technical solution of the present invention, in S2, the hydrogen crushing temperature is 600°C to 800°C and the time is 2 hours; the ball milling time is 10 to 20 hours.
[0023] As a further technical solution of the present invention, in S3, the diffusing agent is DyF3 or TbF3.
[0024] As a further technical solution of the present invention, in S4, the sintering temperature is 1000-1200° C., and the sintering time is 2-4 hours.
[0025] As a further technical solution of the present invention, in S5, the aging treatment includes performing heat preservation treatment on the sintered green body in the first stage, the second stage and the third stage in sequence to obtain a finished product;
[0026] First stage: keep warm at 800℃~900℃ for 2 hours;
[0027] Second stage: keep warm at 500℃~600℃ for 4 hours;
[0028] The third stage: keep warm at 300℃~400℃ for 6 hours.
[0029] In summary, the present invention includes at least one of the following beneficial technical effects:
[0030] (1) In the present application, the coating is completed during the sintering of the raw materials. That is, the raw materials are in full contact with the diffusing agent in the powder state, which enables more comprehensive grain boundary diffusion during the subsequent sintering, making the surface and inner layer grain boundary diffusion effects of the magnet more homogeneous after molding. This not only saves the amount of heavy rare earth, but also eliminates the need to continuously brush the magnet surface, thus saving steps and improving efficiency.
[0031] (2) In the present application, light rare earth is added to replace part of Nd, while ensuring the magnet effect and reducing the material cost, and the amount of heavy rare earth is reduced to less than 2%. The transition metal can refine the grains, improve the coercive force of the material, and optimize the overall composition structure. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Example 1
[0034] The present application designs a method for preparing high-performance NdFeB based on reduced heavy rare earth, comprising the following steps:
[0035] S1, smelting and casting;
[0036] The raw materials are melted in proportion under inert gas protection conditions at a melting temperature of 1500°C for 60 minutes. After melting, they are quickly poured into a preheated copper mold and solidified by rapid cooling to form an ingot to obtain a fine and uniform grain structure.
[0037] The mass percentages of the components in the raw materials are as follows: Nd2Fe14B (96.5%), Ce (1.5%), Dy (1%), Co (0.5%), Cu (0.3%), Al (0.1%), Ga (0.1%);
[0038] S2, hydrogen crushing and ball milling;
[0039] The ingot was subjected to hydrogen crushing treatment to decompose it into fine powder. The hydrogen crushing temperature was 600°C for about 2 hours. The powder was dry-milled under inert gas protection for 10 hours. The powder particle size was 10 μm.
[0040] S3, coating formation;
[0041] The ball-milled powder is immersed in an electrolyte containing DyF3. The solution is uniformly attached to the powder surface by adjusting the voltage and time. The coating thickness is controlled to be 1 μm. The electrolyzed powder is then placed in a drying oven until the powder is completely dry.
[0042] S4, sintering;
[0043] The dried powder is pre-pressed to form a green body with a certain density and shape, and the green body is placed in a sintering furnace protected by vacuum or inert gas, and sintered at a temperature of 1000°C for 2 hours;
[0044] S5, aging treatment;
[0045] The sintered green body is subjected to heat preservation treatment in the first stage, the second stage and the third stage in sequence to obtain a finished product;
[0046] First stage: keep warm at 800℃ for 2 hours;
[0047] Second stage: keep warm at 500℃ for 4 hours;
[0048] Level 3: Keep warm at 300℃ for 6 hours.
[0049] Example 2
[0050] S1, smelting and casting;
[0051] The raw materials are melted in proportion under inert gas protection conditions at a melting temperature of 1600°C for 60 minutes. After melting, they are quickly poured into a preheated copper mold and solidified by rapid cooling to form an ingot to obtain a fine and uniform grain structure.
[0052] The mass percentages of the components in the raw materials are as follows: Nd2Fe14B (96.0%), La (2.0%), Tb (1%), Co (1%), Cu (0.5%), Al (0.3%), Ga (0.2%);
[0053] S2, hydrogen crushing and ball milling;
[0054] The ingot was subjected to hydrogen crushing treatment to decompose it into fine powder. The hydrogen crushing temperature was 800°C for about 2 hours. The powder was dry-milled under inert gas protection for 20 hours. The powder particle size was 20 μm.
[0055] S3, coating formation;
[0056] The ball-milled powder is immersed in an electrolyte containing TbF3. The voltage and time are adjusted to make the solution evenly adhere to the powder surface and the coating thickness is controlled to be 3μm. The electrolyzed powder is then placed in a drying oven until the powder is completely dry.
[0057] S4, sintering;
[0058] The dried powder is pre-pressed to form a green body with a certain density and shape, and the green body is placed in a sintering furnace protected by vacuum or inert gas, and sintered at a temperature of 1200°C for 4 hours;
[0059] S5, aging treatment;
[0060] The sintered green body is subjected to heat preservation treatment in the first stage, the second stage and the third stage in sequence to obtain a finished product;
[0061] First stage: keep warm at 900℃ for 2 hours;
[0062] Second stage: keep warm at 600℃ for 4 hours;
[0063] Level 3: Keep warm at 400℃ for 6 hours.
[0064] Example 3
[0065] S1, smelting and casting;
[0066] The raw materials are melted in proportion under inert gas protection conditions at a melting temperature of 1550°C for 60 minutes. After melting, they are quickly poured into a preheated copper mold and solidified by rapid cooling to form an ingot to obtain a fine and uniform grain structure.
[0067] The mass percentages of the components in the raw materials are as follows: Nd2Fe14B (97%), Ce (1.5%), Dy (0.5%), Co (0.5%), Cu (0.3%), Al (0.1%), Ga (0.1%);
[0068] S2, hydrogen crushing and ball milling;
[0069] The ingot was subjected to hydrogen crushing treatment to decompose it into fine powder. The hydrogen crushing temperature was 700°C and the time was about 2 hours. The powder was dry-milled under inert gas protection for 15 hours. The powder particle size was 15 μm.
[0070] S3, coating formation;
[0071] The ball-milled powder is immersed in an electrolyte containing DyF3. The solution is uniformly attached to the powder surface by adjusting the voltage and time. The coating thickness is controlled at 2μm. The electrolyzed powder is then placed in a drying oven until the powder is completely dry.
[0072] S4, sintering;
[0073] The dried powder is pre-pressed to form a green body with a certain density and shape, and the green body is placed in a sintering furnace protected by vacuum or inert gas, and sintered at a temperature of 1100°C for 3 hours;
[0074] S5, aging treatment;
[0075] The sintered green body is subjected to heat preservation treatment in the first stage, the second stage and the third stage in sequence to obtain a finished product;
[0076] First stage: keep warm at 850℃ for 2 hours;
[0077] Second stage: keep warm at 550℃ for 4 hours;
[0078] Level 3: Keep warm at 350℃ for 6 hours.
[0079] Comparative Example 1
[0080] The difference between the comparative example 1 and the embodiment 1 is that the comparative example 1 is obtained by reversing S3 and S4 in the embodiment 1, that is, sintering is performed first and then the coating is formed.
[0081] Comparative Example 2
[0082] The difference between Comparative Example 2 and Example 2 is that S3 and S4 in Example 1 are reversed to obtain Comparative Example 2, that is, sintering is performed first and then the coating is formed.
[0083] Comparative Example 3
[0084] The difference between Comparative Example 3 and Example 3 is that Comparative Example 3 is obtained by reversing S3 and S4 in Example 3, that is, sintering is performed first and then the coating is formed.
[0085] The finished products obtained from the above-mentioned Examples 1-3 and Comparative Examples 1-3 were cut open, and the performance of the inner layer and the surface layer thereof were tested. The test results are shown in Table 1.
[0086] Table 1
[0087]
[0088]
[0089] It can be seen from the test results of Comparative Examples 1-3 above that the performance of the surface layer and the inner layer of the magnet are quite different in all aspects, which shows that in the case of a single coating, the preparation method in the prior art cannot interfere with the inner layer of the magnet.
[0090] It can be seen from the test results in Examples 1-3 above that the performance of the surface and inner layers of the magnet are similar in all aspects, which shows that in the case of one coating, the preparation method of the present application can penetrate into the inner layer of the magnet and enhance the effect of boundary diffusion to fill every corner of the magnet.
[0091] By comparing the test results of Examples 1-3 and Comparative Examples 1-3, it can be seen that coating the magnet in a powder state can greatly increase the depth of boundary diffusion and make the magnet more homogeneous.
[0092] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing high-performance NdFeB based on reduced heavy rare earth, characterized in that: The steps include: S1, smelting and casting; The raw materials are melted in proportion under inert gas protection conditions, and after melting, they are quickly poured into a preheated copper mold and solidified by rapid cooling to form an ingot to obtain a fine and uniform grain structure; S2, hydrogen crushing and ball milling; The ingot is subjected to hydrogen crushing treatment to decompose it into fine powder, and the powder is dry-milled under argon protection to obtain a powder particle size of 10-20 μm; S3, coating formation; The ball-milled powder is immersed in an electrolyte containing a diffusant, and the solution is uniformly attached to the powder surface by adjusting the voltage and time, and the coating thickness is controlled to be 1 to 3 μm. The electrolyzed powder is then placed in a drying oven until the powder is completely dry. S4, sintering; The dried powder is pre-pressed to form a green body with a certain density and shape, and the green body is placed in a sintering furnace protected by vacuum or inert gas for sintering; S5, aging treatment.
2. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 1, characterized in that: In S1, the raw materials include main material, light rare earth, heavy rare earth and transition metal, wherein the mass ratio of the main material, light rare earth, heavy rare earth and transition metal is (96-97): (1-2): (0.5-1.5): (0.5-1).
3. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 2, characterized in that: In the S1, the main material is Nd2Fe14B, the light rare earth is one of Ce and La, the heavy rare earth is one of Dy and Tb, and the transition metal is one or more of Co, Cu, Al and Ga.
4. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 3, characterized in that: In the step S1, the raw material is smelted at a temperature of 1500°C to 1600°C for 60 minutes.
5. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 3, characterized in that: In the S2, the hydrogen crushing temperature is 600°C to 800°C, the time is 2 hours, and the ball milling time is 10 to 20 hours.
6. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 1, characterized in that: In the S3, the diffusing agent is DyF3 or TbF3.
7. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 1, characterized in that: In the step S4, the sintering temperature is 1000-1200° C., and the sintering time is 2-4 hours.
8. The method for preparing high-performance NdFeB based on reduced heavy rare earth according to claim 1, characterized in that: In S5, the aging treatment includes performing heat preservation treatment on the sintered green body in the first stage, the second stage and the third stage in sequence to obtain a finished product; First stage: keep warm at 800℃~900℃ for 2 hours; Second stage: keep warm at 500℃~600℃ for 4 hours; The third stage: keep warm at 300℃~400℃ for 6 hours.